Application Of Reciprocal Teaching On Material Of Circle - Ayu Silvi Lisvian Sari (IJER (Indonesian Journal of Educational Research), 2021)
The wave of modern society today has changed very rapidly. The flow of information and technology is a strength and power that can determine the dynamics of contemporary life. Development in all fields of education is an effort to educate the nation's life improve the quality of Indonesian human resources and create a just and independent society. However, based on the results of the World Competitiveness Yearbook survey, it was explained that education in Indonesia in 2020 was ranked 40th out of 63 countries surveyed. This situation should be material for thought and introspection for the Indonesian people. Especially in the teaching and learning process that has occurred so far, it still shows the lack of teachers in providing opportunities for students to explore their knowledge, to express their knowledge through creation and creativity. The lack of student experience, in this case, causes students to tend to experience difficulties when faced with new problems To overcome these problems, researchers conducted research using Reciprocal Teaching. The researcher aimed to describe the application of Reciprocal Teaching to the circle material in class VIII SMP Muallimin Wonodadi Blitar. The subjects of this study were students of class VIII semester 2 of Muallimin Middle School Wonodadi Blitar, with a total of 32 students. The object of this research is the whole process of learning mathematics using Reciprocal Teaching. The research instruments are worksheets, observation sheets, and tests. The research steps using Reciprocal Teaching include (1) Grouping students and group discussions, (2) Making questions (Question Generating), (3) Presenting the results of group work. (4) Clarifying the problem (Clarifying). (5) Provide practice questions that contain development questions (Predicting). (6) Summarizing the material studied (Summarizing). After analyzing the data, the researcher concluded that this study obtained classical learning outcomes reaching 87.5%, the average teacher observations reaching 85.83%, and the average student observations reaching 82.5%. So that research with the application of Reciprocal Teaching for circle material, class VIII SMP Muallimin Wonodadi Blitar is said to be successful.